Researching on the Knowledge of Teachers Who Teach Math for Secondary Level Student Understanding - Buhaerah, Buhaerah; Muhammad Ahsanu Haq; Herman Sanjaya (UNNES JOURNAL, 2025)
Although mathematics teachers' expertise in understanding subject matter is widely believed to have a direct impact on students' comprehension and academic achievements, there remains limited empirical research that specifically examines how teachers' content knowledge contributes to student learning outcomes. This study aims to assess the importance of mathematics teachers' competence in the content knowledge required for teaching secondary school mathematics. The research involved 55 secondary mathematics teachers who specialize in SS-level subjects for grades 10–12. Participants were selected through a combination of purposive and convenience sampling, considering their subject expertise and availability. Data were collected using a validated 25-question mathematics subject knowledge test, administered over 60 minutes via EduSuite computer-assisted instruction (CAI) software. The test was designed to evaluate teachers' understanding of essential mathematics topics taught in schools. Data analysis involved descriptive statistics, frequency distributions, and one-way ANOVA to assess the variation in mathematics knowledge and classify achievement levels based on established benchmarks. The findings provide a comprehensive overview of teachers' proficiency in key areas, including algebraic patterns, functions and relationships, space, geometric shapes, measurement, operations, trigonometry, and geometry. These results underscore the significance of strengthening mathematics content knowledge as part of teacher professional development. This study provides a solid foundation for designing targeted training and education programs aimed at improving the quality of mathematics instruction at the secondary level. Future research is recommended to explore the effectiveness of such training programs in enhancing teacher competency and improving student outcomes across different educational settings. Abstrak Meskipun keahlian guru matematika dalam memahami materi pelajaran secara umum diyakini memiliki dampak langsung terhadap pemahaman dan pencapaian akademik siswa, namun masih terdapat keterbatasan penelitian empiris yang secara khusus mengeksplorasi sejauh mana pengetahuan konten guru berkontribusi terhadap hasil belajar siswa. Studi ini bertujuan untuk menilai pentingnya kompetensi guru matematika dalam penguasaan pengetahuan konten yang diperlukan untuk mengajar di tingkat sekolah menengah. Penelitian ini melibatkan 55 guru matematika sekolah menengah yang mengampu mata pelajaran tingkat Secondary School (SS) untuk kelas 10 hingga 12. Para peserta dipilih melalui kombinasi metode purposive dan convenience sampling, dengan mempertimbangkan keahlian dan ketersediaan mereka. Data dikumpulkan menggunakan tes pengetahuan konten matematika yang telah divalidasi, terdiri atas 25 butir soal, dan dilaksanakan selama 60 menit melalui perangkat lunak Computer-Assisted Instruction (CAI) EduSuite. Tes ini dirancang untuk mengukur pemahaman guru terhadap topik-topik esensial dalam kurikulum matematika sekolah menengah. Analisis data dilakukan menggunakan statistik deskriptif, distribusi frekuensi, dan analisis varians satu arah (ANOVA) untuk mengevaluasi variasi dalam tingkat pengetahuan serta mengklasifikasikan pencapaian berdasarkan tolok ukur yang telah ditetapkan. Temuan studi ini memberikan gambaran menyeluruh mengenai tingkat kecakapan guru dalam bidang-bidang utama seperti pola aljabar, fungsi dan relasi, ruang, bentuk geometris, pengukuran, operasi, trigonometri, dan geometri. Hasil tersebut menegaskan pentingnya penguatan pengetahuan konten matematika sebagai bagian integral dari pengembangan profesional guru. Studi ini menjadi landasan strategis untuk merancang program pelatihan dan pendidikan yang terfokus dalam rangka meningkatkan kualitas pembelajaran matematika di tingkat sekolah menengah. Penelitian lanjutan disarankan untuk mengevaluasi efektivitas program pelatihan tersebut dalam meningkatkan kompetensi guru dan mendukung pencapaian hasil belajar siswa di berbagai konteks pendidikan.